Species delimitation and name application in Deyeuxia abnormis, Agrostis zenkeri, A. pleiophylla and related taxa (Poaceae: Agrostidinae) - Paszko, Beata; Soreng, Robert J. (Phytotaxa, 2013)
Historically tangled taxonomy and nomenclature of Deyeuxia abnormis, Agrostis zenkeri, A. pleiophylla and their allies is presented. Deyeuxia abnormis is recognized as a distinct species. Previous descriptions of this taxon were entangled with concepts of Agrostis zenkeri and Deyeuxia diffusa. The typification of Deyeuxia abnormis by Noltie is rejected in favor of the lectotype designated by Bor. The name Deyeuxia abnormis is applied to specimens of this species group with a tufted habit and callus hairs between 0.25 and 0.50 percent of their lemma in length. Specimens previously included in D. abnormis that are characterized by scrambling habit, simple or branched culms, and callus hairs between 0.6 and 1.0 percent of the lemma length, are assigned to D. diffusa. The taxonomy of Deyeuxia abnormis and its allies is clarified and new synonyms are provided, along with amended descriptions, and a key to the complex of D. abnormis and its allies. The distributions of Deyeuxia abnormis and D. diffusa in South Asia are updated. The previous typification of Agrostis pleiophylla is rejected and a new lectotype is selected. The names Anisachne gracilis (= Deyeuxia abnormis) and Agrostis continentalis (= Deyeuxia abnormis) are typified.